Collective rights in artisanal fisheries and the trade-offs in fisheries policies: An analysis of distributive policies - Jara, Miguel; Dresdner, Jorge; Gómez, Walter (Estudios de Economía, 2015)
This research analyzes the potential effects that a redistributive fishing quota policy could have on the profits and employment of the artisanal fisher organizations. We use a multi-objective programming model and apply it to the common sardine and anchovies fisheries in the Biobío Region for year 2011. The results indicate the presence of trade-offs between the equity –profits and equity– employment objectives. Moreover, the results suggest the existence of widespread inefficiencies in the effort allocation within the organizations, independently of the weight given to the different objectives.